Angiolymphoid hyperplasia with eosinophilia: Report of two cases in children - Anupam Das; Anupama Ghosh; Ramesh Chandra Gharami (Wolters Kluwer Medknow Publications, 2016)
Angiolymphoid hyperplasia with eosinophilia (ALHE) is apparently benign, locally proliferating lesion composed of vascular channels with surrounding infiltrate of lymphocytes and eosinophils. We report two cases with long-standing papulonodular lesions on the left ear who presented to us on account of trauma-induced bleeding and cosmetic issues. Peripheral blood eosinophilia was present, and histological findings were consistent with a diagnosis of ALHE. The rarity of this disease in the pediatric age group prompted the present report.